1997
DOI: 10.3109/00365529709007687
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Regulation of Pancreatic Exocrine Secretion in Minipigs

Abstract: A negative feedback regulation of pancreatic exocrine secretion is present in starved minipigs. Duodenal acidity and plasma levels of secretin semm to be of importance, whereas duodenal enzyme activity and the level of CCK in plasma probably are not. A postprandial negative feedback regulation through duodenal enzymatic activity and release of CCK into blood could not be shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…In contrast to the study of Houe et al (1997), presented results confirm the existence of CCK mediated feedback inhibition mechanism exerted by duodenal pancreatic juice under prandial conditions. The CCK blood levels decreased parallel to lowered trypsin/protein output.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In contrast to the study of Houe et al (1997), presented results confirm the existence of CCK mediated feedback inhibition mechanism exerted by duodenal pancreatic juice under prandial conditions. The CCK blood levels decreased parallel to lowered trypsin/protein output.…”
Section: Discussioncontrasting
confidence: 75%
“…The duodenal feedback regulation of pancreatic secretion in fed state by luminal proteases was observed in some (Owyang et al, 1986;Pierzynowski et al, 1999) but not in all studies (Houe et al, 1997). Houe et al (1997) failed to show a postprandial negative feedback regulation through duodenal enzymatic activity and release of CCK into peripheral blood. Moreover, data is still lacking concerning effects on pancreatic exocrine secretion of pancreatic juice or enzymes, bile or bile salts when they are presented in the ileum.…”
Section: Introductionmentioning
confidence: 88%
“…In pigs, there is a controversy concerning the existence of feedback regulation. Bile has been known to affect feedback regulation in animal species other than pigs and in humans, but the mechanism remains unclear (Green and Nasset, 1980;Houe et al, 1997). Some researchers suggested that bile acids may stabilize luminal protease activity resulting in inhibition of CCK release, and others are of the opinion that the inhibition of plasma CCK is achieved due to enhanced somatostatin release by the bile (Koop et al, 1996).…”
Section: Introductionmentioning
confidence: 97%